2021
DOI: 10.1177/09722629211050310
|View full text |Cite
|
Sign up to set email alerts
|

Career Adapt-Abilities Scale-Short Form: Validation for Use in India

Abstract: The Career Adapt-Abilities Scale (CAAS) is popular among researchers and validated in many countries but has not yet been tested for the Indian context. This study examined the CAAS Short Form (CAAS-SF) among a sample of Indian business school students. The CAAS-SF consists of four subscales, each with three items measuring concern, control, curiosity and confidence as psychosocial resources. A sample of 369 Indian business-school students with human resource management as major participated in the scale valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…In the last four years, validation studies on the application of CAAS-SF in some nations have determined that the 12-item CAAS-SF (Maggiori et al, 2015) has a strong correlation with the 24-item CAAS (Savickas and Porfeli, 2012). In Australia (Perera and McIlveen, 2017), Turkey (Işık et al, 2018), Switzerland (Urbanaviciute et al, 2019), China (Yu et al, 2019), Germany (Haenggli and Hirschi, 2020), and India (Pal and Jena, 2021), similar results were found in related studies, and both the reliability as well as the validity of the measure were good. In these studies, it was observed that although the scale was halved in size, the 12-item CAAS-SF displayed the same component structure and psychometric qualities as the 24-item variant.…”
Section: Instruments For Assessing Career Adaptabilitysupporting
confidence: 61%
See 2 more Smart Citations
“…In the last four years, validation studies on the application of CAAS-SF in some nations have determined that the 12-item CAAS-SF (Maggiori et al, 2015) has a strong correlation with the 24-item CAAS (Savickas and Porfeli, 2012). In Australia (Perera and McIlveen, 2017), Turkey (Işık et al, 2018), Switzerland (Urbanaviciute et al, 2019), China (Yu et al, 2019), Germany (Haenggli and Hirschi, 2020), and India (Pal and Jena, 2021), similar results were found in related studies, and both the reliability as well as the validity of the measure were good. In these studies, it was observed that although the scale was halved in size, the 12-item CAAS-SF displayed the same component structure and psychometric qualities as the 24-item variant.…”
Section: Instruments For Assessing Career Adaptabilitysupporting
confidence: 61%
“…CFI and IAS are measured from different perspectives, but their applicability is limited (Johnston, 2016). The CAAS (Savickas and Porfeli, 2012) is the most widely used scale (Yu et al, 2019;Pal and Jena, 2021). The Career Adapt-Ability Scale (CAAS) is a cross-cultural international version created by Savickas and a worldwide research group comprised of professionals and scholars from 18 nations and regions.…”
Section: Instruments For Assessing Career Adaptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, this study was conducted mainly to evaluate the psychometric properties of Malay CAAS to be used on students of higher learning institutions in Malaysia. The analyses were run twice and both Malay-CAAS24 and Malay-CAAS12 yielded good CFA, reliability, and validity, ensuring that CAAS-Malay is reliable and valid to be used among students in higher learning institutions, and the findings were supported by enormous research which studied the adaptation of CAAS in different languages (Akın et al, 2014;Atitsogbe et al, 2019;Cammarosano et al, 2019;Isik et al, 2018;Johnston et al, 2013;Khalid & Ahmad, 2021;McKenna et al, 2016;Pal & Jena, 2021;Panjaitan & Sahrah, 2020;Tien et al, 2012;van Vianen et al, 2012;Yu et al, 2020). Therefore, we concluded that CAAS-Malay is ready to be utilized by the Malaysian population, particularly undergraduates.…”
Section: Discussionmentioning
confidence: 84%
“…Along the same line, the Chinese translated CAAS-SF was evaluated across three contexts (college students, civil servant, and enterprise employees) showed good reliability with coefficient of α more than .70 (Yu et al, 2020). In a sample of Indian business school students, reliability of the whole scale showed excellent reliability with α = .94, hence was considered reliable and valid (Pal & Jena, 2021).…”
Section: Introductionmentioning
confidence: 95%